Mass flux analysis of 137Cs plumes emitted from the Fukushima Daiichi nuclear power plant. Issue 1 (1st January 2018) - Sekiyama, Tsuyoshi Thomas; Iwasaki, Toshiki
Abstract: The flow vectors of radioactive cesium-137 ( 137 Cs) plume emitted from the Fukushima Daiichi nuclear power plant in March 2011 were quantitatively depicted by a mass flux analysis in this study. 137 Cs plumes were calculated by an Eulerian dispersion model with a 3-km horizontal resolution. The vertically column-integrated mass flux was consistent with the flow approximation based on ground surface 137 Cs observations, even though there were some discrepancies that were caused by differences in the wind direction between the ground surface and the dominant plume layer. These discrepancies were explained by combining the use of the ground surface horizontal mass flux with the column-integrated mass flux. The mass flux analysis clearly provided an illustration of 137 Cs dominant stream locations, directions, and depositions by reducing high-dimensional model outputs into a lower-dimensional plot. Mass flux (i.e. the product of the mass density and wind velocity) has often been used in dynamic meteorology but has not been used as frequently in atmospheric chemistry or pollutant dispersion studies. However, the concept of mass flux is a robust alternative for conventional validation approaches that only utilize a time series of pollutant concentrations. Mass flux analyses can be used further in atmospheric chemistry as a quantitative visualization tool to track the emission, advection, dispersion, and deposition of atmospheric constituents.